2017
DOI: 10.1002/jmv.24931
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the performance in detection of HPV infections between the high‐risk HPV genotyping real time PCR and the PCR‐reverse dot blot assays

Abstract: A new multiplex real-time PCR assay, the high-risk HPV genotyping real time PCR assay (HR HPV RT-PCR), has been developed to detect 15 high-risk HPV types with respective viral loads. In this report, a total of 684 cervical specimens from women diagnosed with vaginitis were assessed by the HR HPV RT-PCR and the PCR reaction and reverse dot blot (PCR-RDB) assays, using a PCR-sequencing method as a reference standard. A total coincidence of 97.7% between the HR HPV RT PCR and the PCR-RDB assays was determined wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 21 publications
3
17
0
1
Order By: Relevance
“…After amplification, HPV genotyping was performed by RDB hybridization on nitrocellulose membrane strips fixed with different HPV type-specific probes. Our study and previous studies [ 17 , 23 ] have demonstrated that the PCR-RDB HR-HPV genotyping assay is an effective HR-HPV genotyping detection method.…”
Section: Methodssupporting
confidence: 65%
See 1 more Smart Citation
“…After amplification, HPV genotyping was performed by RDB hybridization on nitrocellulose membrane strips fixed with different HPV type-specific probes. Our study and previous studies [ 17 , 23 ] have demonstrated that the PCR-RDB HR-HPV genotyping assay is an effective HR-HPV genotyping detection method.…”
Section: Methodssupporting
confidence: 65%
“…Unit costs were taken from the Fujian medical price database. [17,23] have demonstrated that the PCR-RDB HR-HPV genotyping assay is an effective HR-HPV genotyping detection method.…”
Section: Discussionmentioning
confidence: 99%
“…Also there is a window period between the viral infection and Table 1 Summary of emerging viruses with abbreviations: molecular (mol), serological (ser), reverse transcription loop-mediated isothermal amplification (RT-LAMP), immunoglobulin type M (IgM), lateral flow assay (LFA), nonstructural protein (NS1), immunoglobulin type G (IgG), loop mediated isothermal amplification (LAMP), digital PCR (dPCR) enzyme-immunoassay (EIA) and IgM antibody capture ELISA (MAC-ELISA), double antibody sandwich ELISA (DAS-ELISA), enzyme linked immunospotting (ELISPOT), data not available (N.A. 1F), dot-blot (Zhang et al, 2018a), or Southern blotting (Cai et al, 2013), but their sensitivity is insufficient. (Hewa et al, 2009;Jung et al, 2015a) antibody production resulting in false negative results using immunoassays, which can be up as long as 35-45 days for first generation HIV testing (Cornett and Kirn, 2013).…”
Section: Conventional Techniques For Detection Of Viral Diseasesmentioning
confidence: 99%
“…The increase sensitivity acquired in fourth generation of immunoassays led to shortening this window to 10-15 days (Branson and Stekler, 2011). A number of alternative NA techniques have been developed including NA sequence-based amplification (Lanciotti and Kerst, 2001), strand displacement amplification (Shi et al, 2014), or branched DNA probes (Zhang et al, 2018a). Several techniques can directly detect specific viral DNA or RNA via in-situ hybridization (Pfankuche et al, 2018) (Fig.…”
Section: Conventional Techniques For Detection Of Viral Diseasesmentioning
confidence: 99%
“…Усі пацієнтки були обстежені на ВПЛ високоонкогенних типів методом полімеразної ланцюгової реакції (ПЛР) з кількісним визначенням [8]. Оцінку експресії імуноцитохімічних біомаркерів р16 і Кі-67 проводили на діагностичному етапі в цитологічному матеріалі [6].…”
Section: матеріали та методи дослідженьunclassified